Additive interaction between hepatitis B virus infection and tobacco smoking on the risk of gastric cancer in a Chinese population - Danjing Chen; Rong Yu; Yongfeng Cai; He Zhang; Yijun Jiang; Yunli Wu; Xian-E Peng (Infectious Agents and Cancer)
Abstract Objective Although hepatitis B virus (HBV) infection was regarded as a risk factor for liver cancer, the association of HBV infection with gastric cancer (GC) is unclear. In this study, we aim to assess the association of HBV infection with the risk of GC and explore the interaction between HBV infection and other risk factors. Methods A case-control study was conducted and 409 GC cases and 1275 healthy controls were enrolled in Fujian province, China. Serum hepatitis B surface antigen (HBsAg) was measured and epidemiological data were collected. The association between HBV infection and GC risk was analyzed using logistic regression and meta-analysis method was employed to make estimates more conservative. Meanwhile, multiplicative and additive models were used to explore the interaction between HBV infection and other risk factors. Results The prevalence of serum HBsAg positivity was 13.20% among GC cases and 6.20% among controls. Compared to HBsAg-negative subjects, the adjusted odds ratios (OR) for HBsAg positive were 3.30 [95% confidence interval (CI): (1.84–5.91)]. Compared to HBsAg-negative never smokers, the adjusted OR was 2.00 (95%CI: 1.19–3.34) for HBsAg-negative ever smokers,4.27 (95%CI: 1.97–9.26) for HBsAg-positive never smokers, and 4.73 (95%CI: 1.85–12.08) for HBsAg-positive ever smokers. These evidences indicated super-additive [API (95%CI): 0.78 (0.67–0.90), S (95%CI): 5.45 (3.26–9.08)] between HBV infection and tobacco smoking. No interaction between HBV infection and alcohol drinking was found on the risk of GC. Conclusions HBV infection increased the risk of GC, and tobacco smoking and HBV infection may positively interact in the development of GC.